BCT507: Bio-Composite Strength Lab / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2018)
Fundamentals behaviour of materials: metal, wood, plastics, bituminous, cement concrete and bio-materials. Effect of atomic and anatomical microscopic and microscopic structes on behaviour, testing techniques and materials testing standards.